Depressive symptoms are frequent among drug users, but not associated with hepatitis C infection. (August 2014) - Madsen, Lone W.; Fabricius, Thilde; Hjerrild, Simon; Hansen, Thomas M.; Mössner, Belinda K.; Birkemose, Inge; Skamling, Merete; Christensen, Peer B.
Abstract Aim: To compare the prevalence and severity of depressive symptoms among drug users with and without hepatitis C virus (HCV) infection. Methods: This was a cross-sectional survey study carried out at the 2 major drug treatment centres on the island of Funen, Denmark. Participants were drug users presenting to the 2 treatment centres. Individuals with chronic hepatitis B virus or HIV infection were excluded. Participants completed the Major Depression Inventory (MDI) questionnaire when presenting at the centres. Patients with MDI scores indicating severe depression (total MDI score ≥ 35) were referred for treatment evaluation. Hepatitis C status was classified by the presence of anti-HCV as a marker of HCV exposure and HCV-RNA as a marker of ongoing infection. Results: Two hundred and sixty-eight patients were included, of whom 235 (88%) had complete serological testing; 100 (43%, 95% confidence interval (CI) 36–49%) had chronic hepatitis C. The median MDI score was 22 (interquartile range 12–33); 32% (95% CI 26–39%) had a score compatible with depression and 14% (95% CI 10–19%) were rated as severe depression. Depression was not associated with hepatitis C (HCV-infected 29%, non-infected 35%; p = 0.25). Forty-one percent (11/27) of the evaluated participants started antidepressant treatment. Conclusions: Our study demonstrated a high prevalence of depressive symptoms among drug users, but this was not more frequent among HCV-infected patients. The high overall prevalence of depression underlines the relevance of screening for depression in patients who are drug users.